Amylin deposition in the brain: A second amyloid in Alzheimer disease?. Issue 4 (12th July 2013) - Jackson, Kaleena; Barisone, Gustavo A.; Diaz, Elva; Jin, Lee‐way; DeCarli, Charles; Despa, Florin
<x xml:space="preserve">Abstract</x> Objective Hyperamylinemia, a common pancreatic disorder in obese and insulin‐resistant patients, is known to cause amylin oligomerization and cytotoxicity in pancreatic islets, leading to β‐cell mass depletion and development of type 2 diabetes. Recent data has revealed that hyperamylinemia also affects the vascular system, heart, and kidneys. We therefore hypothesized that oligomerized amylin might accumulate in the cerebrovascular system and brain parenchyma of diabetic patients. Methods Amylin accumulation in the brain of diabetic patients with vascular dementia or Alzheimer disease (AD), nondiabetic patients with AD, and age‐matched healthy controls was assessed by quantitative real time polymerase chain reaction, immunohistochemistry, Western blot, and enzyme‐linked immunosorbent assay. Results Amylin oligomers and plaques were identified in the temporal lobe gray matter from diabetic patients, but not controls. In addition, extensive amylin deposition was found in blood vessels and perivascular spaces. Intriguingly, amylin deposition was also detected in blood vessels and brain parenchyma of patients with late onset AD without clinically apparent diabetes. Mixed amylin and amyloid β (Aβ) deposits were occasionally observed. However, amylin accumulation leads to amyloid formation independent of Aβ deposition. Tissues infiltrated by amylin showed increased interstitial space, vacuolation, spongiform change, and capillaries bent at amylin accumulation sites. Unlike the pancreas, there was no evidence of amylin synthesis in the brain. Interpretation Metabolic disorders and aging promote accumulation of amylin amyloid in the cerebrovascular system and gray matter, altering microvasculature and tissue structure. Amylin amyloid formation in the wall of cerebral blood vessels may also induce failure of elimination of Aβ from the brain, thus contributing to the etiology of AD. Ann Neurol 2013;74:517–526